Characterization of the glucansucrase GTF180 W1065 mutant enzymes producing polysaccharides and oligosaccharides with altered linkage composition. (15th February 2017) - Meng, Xiangfeng; Pijning, Tjaard; Tietema, Martin; Dobruchowska, Justyna M.; Yin, Huifang; Gerwig, Gerrit J.; Kralj, Slavko; Dijkhuizen, Lubbert
Highlights: Glucansucrase enzymes of lactic acid bacteria catalyze the synthesis of α-glucans from sucrose. Tryptophan-1065 is critical but not essential for the activity of glucansucrase GTF180-ΔN. Tryptophan-1065 mutants produced α-glucans with changed linkage composition. The stacking interaction at position 1065 is essential for polysaccharide synthesis. Abstract: Exopolysaccharides produced by lactic acid bacteria are extensively used for food applications. Glucansucrase enzymes of lactic acid bacteria use sucrose to catalyze the synthesis of α-glucans with different linkage compositions, size and physico-chemical properties. Crystallographic studies of GTF180-ΔN show that at the acceptor binding sites +1 and +2, residue W1065 provides stacking interactions to the glucosyl moiety. However, the detailed functional roles of W1065 have not been elucidated. We performed random mutagenesis targeting residue W1065 of GTF180-ΔN, resulting in the generation of 10 mutant enzymes that were characterized regarding activity and product specificity. Characterization of mutant enzymes showed that residue W1065 is critical for the activity of GTF180-ΔN. Using sucrose, and sucrose (donor) plus maltose (acceptor) as substrates, the mutant enzymes synthesized polysaccharides and oligosaccharides with changed linkage composition. The stacking interaction of an aromatic residue at position 1065 is essential for polysaccharide synthesis.